Outcomes of pregnancies complicated by haemoglobin H‐constant spring and deletional haemoglobin H disease: A retrospective cohort study. (30th June 2022) - Ake‐sittipaisarn, Srimeunwai; Sirichotiyakul, Supatra; Srisupundit, Kasemsri; Luewan, Suchaya; Traisrisilp, Kuntharee; Tongsong, Theera
Summary: The objective of the study was to compare the maternal and foetal outcomes of pregnancies complicated by Hb H‐constant spring (HbH‐CS) disease/deletional HbH (HbH‐del) disease and low‐risk pregnancies. A retrospective cohort research was undertaken on singleton pregnancies with Hb H‐CS and Hb H‐del diseases. The controls were randomly selected with a control‐to‐case ratio of 10:1. A total of 55 cases of HbH‐CS disease, 231 cases of HbH‐del disease and 2860 controls were compared. The mean gestational age at delivery and birthweight were significantly lower in the HbH‐CS group than in the HbH‐del and control groups. The clinical course of Hb H‐CS was more severe than that of HbH‐del disease. The rates of preterm birth, foetal growth restriction and low birthweight were significantly increased in the HbH‐CS and Hb H‐del groups. These rates were significantly greater in the HbH‐CS group than in the H‐del group. The maternal outcomes were not significantly different among the three groups. In conclusion, pregnancy worsens the course of HbH disease, more noticeably in HbH‐CS disease. Hb H disease significantly increases the risk of adverse foetal outcomes, more noticeably in the HbH‐CS group. Pregnancy is relatively safe for women with HbH disease.